2004
DOI: 10.4314/ajoh.v1i1.31302
|View full text |Cite
|
Sign up to set email alerts
|

Dental caries and extractions of permanent teeth in Jos, Nigeria

Abstract: To determine the effect of tooth morphology and positioning on the occurrence of dental caries in permanent teeth. Design: Retrospective study. Method: Data was extracted from the case notes of patients that underwent extraction at the Plateau State Dental Centre, Jos, Nigeria from January 2000 to December 2001, as a result of dental caries and its sequalae. Result: 12696 patients attended the clinic, with a total of 11546-teeth extracted. 6145 (53.2%) permanent teeth were extracted due to caries and it's sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 5 publications
0
17
0
1
Order By: Relevance
“…Although the first molars extracted in all quadrants were 29.0%, this was not significantly different from the second molars (27.2%) extracted P > 0.05. However, previous studies from Nigeria recorded 41.6% 2 and 50%, [16] respectively. While a UAE study [15] reported extraction of upper molars more frequently than the lower molars in the study, our study shows that lower molars were extracted more than the upper molars.…”
Section: Discussionmentioning
confidence: 86%
“…Although the first molars extracted in all quadrants were 29.0%, this was not significantly different from the second molars (27.2%) extracted P > 0.05. However, previous studies from Nigeria recorded 41.6% 2 and 50%, [16] respectively. While a UAE study [15] reported extraction of upper molars more frequently than the lower molars in the study, our study shows that lower molars were extracted more than the upper molars.…”
Section: Discussionmentioning
confidence: 86%
“…Likewise, some researchers[911] in other regions of Nigeria have also published their findings on reasons for teeth mortality. A critical scrutiny of these results shows that there have been considerable variations in their findings as regards the most important etiological factors responsible for teeth mortality.…”
Section: Discussionmentioning
confidence: 99%
“…[512] This may be due to transition from the customary fibrous diet to western diet. [911] These researchers have shown from their studies that the incidence of dental caries and periodontal diseases are on the increase as refined sugar, fruit drinks, and sweet have become readily available in Nigeria. Other reasons identified for extraction of teeth in this study have been reported earlier by other researchers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Moreover, permanent first molar extractions top the data for the rate and incidence of extractions as compared to other teeth. 5 Since the occlusal surface of young permanent first molars is susceptible to caries and the caries on these surfaces begin soon after the eruption, early sealing is indicated as suggested by Melgar et al 6 and supported by various other authors. [1][2][3][4][5] Traditionally epidemiologic indices have been proposed to evaluate variations in the incidence of new lesions and the progression of the existing dental lesions.…”
Section: Introductionmentioning
confidence: 96%